Auger electron angular distributions following excitation or ionization of the I 3d level in methyl iodide - Forbes, Ruaridh; De Fanis, Alberto; Bomme, Cédric; Rolles, Daniel; Pratt, Stephen T.; Powis, Ivan; Besley, Nicholas A.; Nandi, Saikat; Milosavljević, Aleksandar R.; Nicolas, Christophe; Bozek, John D.; Underwood, Jonathan G.; et al. (AIP Publishing, 2018)
Auger electron spectra following excitation or ionization of the I 3d level in CH3I have been recorded with horizontally or vertically plane polarized synchrotron radiation. These spectra have enabled the Auger electron angular distributions, as characterized by the β parameter, to be determined. The I 3d photoionization partial cross section of CH3I has been calculated with the continuum multiple scattering approach, and the results show that in the photon energy range over which Auger spectra were measured, the I 3d cross section exhibits an atomic-like behavior and is dominated by transitions into the εf continuum channel. In this limit, the theoretical value of the alignment parameter (A20) characterizing the core ionized state in an atom becomes constant, independent of photon energy. This theoretical value has been used to obtain the Auger electron intrinsic anisotropy parameters (α2) from the β parameters extracted from our normal (non-resonant) molecular Auger spectra. The resulting anisotropy parameters for the M45N45N45 transitions in CH3I have been compared to those calculated for the corresponding transitions in xenon, and the experimental and theoretical results are in good agreement. Anisotropy parameters have also been measured for the M45N1N45, M45N23N45, and M45N45O23 transitions. For the M45N1N45 and M45N23N45 Auger decays in CH3I, the experimentally derived angular distributions do not exhibit the strong dependence on the final ionic state that is predicted for these transitions in xenon. Resonantly excited Auger spectra have been recorded at 620.4 and 632.0 eV, coinciding with the I 3d5/2 → σ* and 3d3/2 → σ* transitions, respectively. The resulting Auger electron angular distributions for the M4N45N45 and M5N45N45 decays were found to exhibit a higher anisotropy than those for the normal process. This is due to the larger photo-induced alignment in the neutral core excited state. For a particular Auger transition, the Auger electron kinetic energy measured in the resonantly excited spectrum is higher than that in the normal spectrum. This shift, due to the screening provided by the electron excited into the σ* orbital, has been rationalized by calculating orbital ionization energies of I 3d excited and I 3d ionized states in CH3I.